Gender, institutions, and economic development: Findings and open research and policy issues - Stephan Klasen (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2016)
Gender relations are a key institution governing important aspects of production and reproduction of societies. They are guided by formal institutions as well as informal norms and values. As this survey shows, there is great regional heterogeneity in gender inequality in formal and informal social institutions. The literature on long-term drivers of gender gaps suggests that those gender gaps are related to long-standing and regularly reproduced gender norms and values related to differences in women's economic opportunities and constraints. The paper also shows that these gender gaps not only affect gender equity but overall development outcomes such as economic growth and reductions in mortality. This is best documented in the case of gender gaps in education but there is also evidence for the negative effects gender of gaps in employment, political and economic empowerment, access to resources, and social institutions on development outcomes. The paper then shows that there has been a large and heterogeneous change in gender gaps. While gender gaps in education (and legal rights) have closed very rapidly, gender gaps in labor force participation, health, political participation, and time use have closed much less rapidly, and there has been virtually progress in reducing occupational and sectoral segregation, unexplained gender pay gaps, and violence against women. The paper presents some hypotheses that might explain this differential performance and also contribute to understanding regional dynamics, before pointing towards a forward-looking research agenda on better understanding the linkages between institutions and their change, gender inequality, and economic development.
Keywords: D63; J71; O15; 330; gender; institutions; economic development